2015
DOI: 10.1088/0031-9155/61/1/n11
|View full text |Cite
|
Sign up to set email alerts
|

Dose rate dependence of the PTW 60019 microDiamond detector in high dose-per-pulse pulsed beams

Abstract: Recombination effects can affect the detectors used for the dosimetry of radiotherapy fields. They are important when using ionization chambers, especially in liquid-filled ionization chambers, and should be corrected for. The introduction of flattening-filter-free accelerators increases the typical dose-per-pulse used in radiotherapy beams, which leads to more important recombination effects. Diamond detectors provide a good solution for the dosimetry and quality assurance of small radiotherapy fields, due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 40 publications
(50 reference statements)
3
17
0
2
Order By: Relevance
“…While the response of the Diode E changes by up to 3% in the DPP range of 0.13 mGy/pulse to 0.86 mGy/pulse, the microSilicon exhibits a lower DPP dependence comparable to that of the microDiamond, where the detector’s response changes by less than 1%. The DPP dependence of the microDiamond detector agrees with the results published by Brualla‐González et al For the axial orientation, the EPOM of the microSilicon was found to lie 0.7 ± 0.2 mm below the detector’s outer front surface, which is comparable to the manufacturer’s specification of 0.8 mm.…”
Section: Discussionsupporting
confidence: 89%
“…While the response of the Diode E changes by up to 3% in the DPP range of 0.13 mGy/pulse to 0.86 mGy/pulse, the microSilicon exhibits a lower DPP dependence comparable to that of the microDiamond, where the detector’s response changes by less than 1%. The DPP dependence of the microDiamond detector agrees with the results published by Brualla‐González et al For the axial orientation, the EPOM of the microSilicon was found to lie 0.7 ± 0.2 mm below the detector’s outer front surface, which is comparable to the manufacturer’s specification of 0.8 mm.…”
Section: Discussionsupporting
confidence: 89%
“…The dose‐rate in beam quality Q was in this range, and no dose‐rate corrections were applied to detector readings in in‐phantom measurements in HDR 192 Ir beams. It is known that the level of impurities and defects in a crystal affects the signal of a diamond detector, and their presence can be assessed indirectly in terms of dose‐rate dependence and preirradiation dose . The nearly identical responses of all microDiamonds in short‐term stability measurements suggest that the detectors used in the present study do not differ in terms of their crystal properties that might influence dose‐rate dependence and stabilization of a detector.…”
Section: Resultsmentioning
confidence: 82%
“…A detailed description of its structure and detection properties can be found elsewhere . Characterization in high‐energy photon beams showed that it has linear response to dose from 0.5 to 15 Gy, good stability, negligible dose‐rate dependence, uniform energy response (including low‐energy scattered photons) and low angular and temperature dependences . Since dosimetry of HDR 192 Ir BT sources is similar to that of small photon fields in terms of high dose gradients and high dose rates, these findings, coupled with near water‐equivalence of carbon, direct readout and convenience of use, suggest that the microDiamond would be suitable for the determination of absorbed dose to water in HDR 192 Ir beams.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Our results hence do not contradict findings in high-energy photon and electron beams reporting negligible beam quality dependence. 1,38,39 Furthermore, no significant relative intrinsic energy dependence was observed in our previous study 9 of microDiamond detectors in 192 Ir beam which had an effective photon energy close to 300 keV.…”
Section: A2 MC Simulations Of Effects Associated With Detector Dementioning
confidence: 71%